2006
DOI: 10.1021/bi052382x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Metabolites in Mouse Models of Congenital Blinding Diseases:  Formation and Storage of Retinyl Esters

Abstract: Regeneration of the visual chromophore, 11-cis-retinal, is a critical step in restoring photoreceptors to their dark-adapted conditions. This regeneration process, called the retinoid cycle, takes place in the photoreceptor outer segments and the retinal pigment epithelium (RPE). Disabling mutations in nearly all of the retinoid cycle genes are linked to human conditions that cause congenital or progressive defects in vision. Several mouse models with disrupted genes related to this cycle contain abnormal fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 48 publications
4
31
0
Order By: Relevance
“…Extensive studies in animals, including rats as well as WT and Abca4 −/− Rdh8 −/− double-KO mice that closely mimic many features of human retinal degeneration, showed that Ret-NH 2 exhibits a protective effect against lightinduced damage by preventing buildup of atRAL and its condensation products (7,33,50,51). But, Ret-NH 2 is (a) used as a substrate by LRAT, (b) a less potent inhibitor of RPE65 than emixustat, and (c) metabolized to retinol in vivo (7,26,33,35,39,50,(52)(53)(54). First, Ret-NH 2 is retained in the eye by the action of LRAT that produces its amidated precursor, and then the resulting retinyl amide is slowly hydrolyzed to evoke a long-lasting suppression of retinoid isomerase activity (35).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies in animals, including rats as well as WT and Abca4 −/− Rdh8 −/− double-KO mice that closely mimic many features of human retinal degeneration, showed that Ret-NH 2 exhibits a protective effect against lightinduced damage by preventing buildup of atRAL and its condensation products (7,33,50,51). But, Ret-NH 2 is (a) used as a substrate by LRAT, (b) a less potent inhibitor of RPE65 than emixustat, and (c) metabolized to retinol in vivo (7,26,33,35,39,50,(52)(53)(54). First, Ret-NH 2 is retained in the eye by the action of LRAT that produces its amidated precursor, and then the resulting retinyl amide is slowly hydrolyzed to evoke a long-lasting suppression of retinoid isomerase activity (35).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei are stained with Hoechst 33342 (blue). (Golczak et al, 2005a,b;Maeda et al, 2006), with a prolonged mode of action because of its reversible amidation. Thus, the suppression of the visual function depends on the level of the accumulated amides of Ret-NH 2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype in rgr −/− mice is mild (94). These mice show reduced 11-cis-RAL and rhodopsin levels in the retina following light exposure, and increased all-trans-and 13-cis-retinyl esters in the RPE (94,95,135). Slightly decreased ERG responses are also seen, commensurate with the decreased levels of rhodopsin.…”
Section: Dominant and Recessive Rp Due To Mutations In The Rgr Genementioning
confidence: 99%